Resilience in Resistance: The Role of Cell Wall Integrity in Multidrug-Resistant Candida - Iván A. Banda-Flores; David Torres-Tirado; Héctor M. Mora-Montes; Gabriela Pérez-Flores; Luis A. Pérez-García (Journal of Fungi)
The Candida species cell wall plays a pivotal role as a structural and functional barrier against external aggressors and as an intermediary in host–pathogen interactions. Candida species exhibit unique adaptations in their cell wall composition, with varying proportions of chitin, mannans, and β-glucans influenced by the environmental conditions and the morphological states. These components not only maintain cellular viability under osmotic, thermal, and chemical stress, but also serve as the key targets for novel antifungal strategies. MAPK signaling pathways, like the cell wall integrity pathway and the high-osmolarity glycerol pathway, play a crucial role in responding to cell wall stressors. Due to the rise of antifungal resistance and its clinical challenges, there is a need to identify new antifungal targets. This review discusses the recent advances in understanding the mechanisms underlying cell wall integrity, their impact on antifungal resistance and virulence, and their potential as therapeutic targets of C. albicans, N. glabratus, and C. auris.